2018
DOI: 10.21767/2573-0320-c2-005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of malaria parasites after treatment in travelers: A 12-months longitudinal study and statistical modelling analysis

Abstract: The rapid clearance of malaria parasite DNA from circulation has widely been accepted as a fact without being systemically investigated. We assessed the persistence of parasite DNA in travelers treated for Plasmodium falciparum malaria in a malaria-free area. Venous blood was collected at the time of admission and prospectively up to one year. DNA and RNA were extracted and analyzed using species-specific and gametocyte-specific real-time PCR as well as merozoite surface protein 2 (msp2)-PCR. In 31 successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
3
12
1
Order By: Relevance
“…In addition to isolation and freezing of PBMCs at each follow-up, samples were also collected for antibody analysis (serum or plasma), blood chemistry and microscopy, and PCR and blood smears for detection of malaria parasites. Part of the cohort has been described previously for telomere dynamics (49) and parasite prevalence after treatment (50). For some time points and study participants, only plasma or cells were available, explaining the different (n) included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to isolation and freezing of PBMCs at each follow-up, samples were also collected for antibody analysis (serum or plasma), blood chemistry and microscopy, and PCR and blood smears for detection of malaria parasites. Part of the cohort has been described previously for telomere dynamics (49) and parasite prevalence after treatment (50). For some time points and study participants, only plasma or cells were available, explaining the different (n) included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Only people carrying gametocytes can be infectious to mosquitoes. Recent studies showed that microscopy is insufficiently sensitive to detect low densities of asexual parasites and gametocyte [25,26]. In most endemic settings, a small proportion of infecting parasites are gametocytes [27].…”
Section: Parasite-vector Interplay For the Transmission Successmentioning
confidence: 99%
“…Post-treatment detection of parasite DNA may re ect both (remnants of) asexual parasites and gametocytes (6,7), the latter commonly persisting after ACT treatment (8). A study in travelers in Sweden (9) indicated that residual parasite DNA can be detected by qPCR for up to 42 days after successful treatment without evidence of viable asexual parasites or gametocytes. Recently, mRNA transcripts speci c to ring-stage parasites (skeleton binding protein; sbp1) were reported following ACT treatment (6,10).…”
Section: Introductionmentioning
confidence: 99%